Chemical composition of leaf essential oils of Lantana camara varieties in South Africa and their effect on the behavioural preference of Falconia intermedia - Ngxande-Koza, Samella W (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
Lantana camara L. (Verbenaceae) is one the most problematic invaders in South Africa invading forest edges, sand dunes, and shorelines by forming impenetrable thickets. Lantana camara invasions degrade natural biodiversity, reduce the value of land and consequently it has been a target for biological control, over the last 50 years in South Africa. Studies that have reported on chemical profile of Lantana camara have been conducted around the world but not in South Africa. Hence, the first aim of the current study was to identify the chemical baseline of L. camara varieties in the Eastern Cape, South Africa. Recent studies have shown that feeding by one of the agents released against L. camara, Falconia intermedia (Distant) (Hemiptera: Miridae), induces anti-herbivory response through increased leaf toughness and trichome density. A preliminary study conducted also reported the production of volatile chemicals by one variety, Whitney Farm, due to feeding by the mirids. Therefore, the second aim was to determine the induced changes in chemical compounds of L. camara varieties after feeding by F. intermedia. A third aim was to determine the effect these chemical compounds have on the behaviour of F. intermedia. To identify the chemical baseline of L. camara varieties, the essential oils of four L. camara varieties (East London, Port Alfred, Whitney Farm and Heather Glen) were analysed using gas chromatography mass spectrometry (GC-MS) and that resulted to the identification of 163 constitutive and 75 induced chemicals across the varieties tested. Lantana camara varieties showed different chemical classes but were highly dominated by terpenes. A great variation in the number of constitutive chemical compounds was found in all the varieties. There were 56 constitutive chemical compounds in the Whitney Farm variety, 41 in the East London variety, 36 in the Heather Glen variety and 30 in the Port Alfred variety. The Whitney Farm variety had the highest number (22) of unique constitutive chemicals identified when compared with other varieties. This indicates the chemical distinctiveness of the Whitney Farm variety from the other varieties. In the varieties tested, there were common chemical compounds identified in constitutive and induced (discussed below) states of the plants such as caryophyllene, hexane, naphthalene, copaene and a-caryophyllene. Besides naphthalene, the majority of chemical compounds in South African L. camara varieties were similar to compounds that have been identified across the world, suggesting that they are closely related. The expression of naphthalene in these varieties may be due to changes in the chemicals expressed over evolutionary time as predicted by the Novel Weapons Hypothesis. Amongst the varieties, a great variation in chemical compounds and their concentrations was shown in the induced states of the plants. The concentration of constitutive caryophyllene ranged from (3.13 - 15.7) %, to (4.02 - 11.10) % after feeding. The concentration of constitutive hexane ranged from (6.13 - 71.19) %, to (33.3 - 75.8) % after feeding. The concentration of constitutive naphthalene ranged from (0.21 - 4.79) %, to (0.92 - 2.11) % after feeding. The concentration of constitutive copaene ranged from (0.57 - 1.57) %, to (1.20 - 2.72) %. Lastly, the concentration of constitutive a-caryophyllene ranged from (1.18 - 9.03) %, to (0.78 - 5.48) % after feeding. The changes in chemical concentrations in lantana varieties indicated that feeding by the mirid on L. camara varieties causes an induction by either reducing or increasing the chemical concentrations. To determine the effect of the identified compounds on the behaviour of F. intermedia adults, olfactometer bioassays were conducted using a Y-tube technique. A significantly higher proportion of F. intermedia were attracted to undamaged leaves over damaged leaves and purified air. Undamaged leaves attracted 52 % of F. intermedia from the East London variety, 62.5 % from the Port Alfred variety, 56 % from the Whitney Farm variety, 58 % from the Lyndhurst variety and 54.5 % from the Heather Glen variety in dual choice trials versus damaged leaves. Furthermore, a significantly higher proportion of F. intermedia were attracted to damaged leaves over purified air. Damaged leaves attracted 67 % of F. intermedia from the East London variety, 67 % from the Port Alfred variety, 65.9 % from the Whitney Farm variety, 65.3 % from the Heather Glen variety and 64.5 % from the Lyndhurst variety. Olfactometer bioassays were also conducted using purified standard compounds of four chemical compounds identified from essential oils, hexane was used as a positive control as it is reported to be an insect attractant in literature. Hexane was highly attractive to the mirids compared to three standard compounds caryophyllene, caryophyllene oxide and naphthalene at the rate of 80 %, 73 % and 80 %, respectively. The standard compounds tested against F. intermedia are major compounds contained by L. camara varieties and they have proven to have a repellent effect. This may indicate that after feeding by F. intermedia, the major compounds expressed by the plant varieties repel F. intermedia contributing to the invasiveness of this weed. The increased expression of hexane and caryophyllene after feeding may also indicate increased attraction to some insects, opening up the potential for third trophic level interactions in varieties where this is the case. This is the first study on the chemical composition of essential oils of L. camara in South Africa. Therefore, we recommend that where appropriate chemical profile studies of the invasive alien plants should be considered during host specificity testing, and the vital role of chemical compounds on agent-weed interactions must be taken into consideration with other factors before and after the biological control agents are released.
Keywords: Uncatalogued